OPTIMIZATION OF ENGLISH LANGUAGE LEARNING USING PREZI IN THE EDUCATIONAL TECHNOLOGY PROGRAM - Sinaga, Andromeda Valentino; Sianipar, Rimma (Media Inovasi Pendidikan dan Pembelajaran, 2025)
This research seeks to evaluate the impact of utilizing Prezi as an instructional tool to improve students' interest in learning, comprehension of concepts, and English language proficiency within the Educational Technology program. The study employs a classroom action research (CAR) design involving students as research subjects. Data were gathered using surveys, direct observations, and structured interviews. The findings indicate that the use of Prezi significantly increases students' interest in learning English. Additionally, students demonstrate improved conceptual understanding and language skills. These findings suggest that Prezi is an effective learning medium for enhancing the quality of English language instruction, particularly in the context of higher education.